The MBOAT7 rs641738 variant is associated with an improved outcome in primary sclerosing cholangitis - Freund, Cora; Wahlers, Arne; Haji Begli, Nima; Leopold, Yvonne; Klöters-Plachky, Petra; Mehrabi, Arianeb; Mohr, Isabelle; Sander, Julia; Rupp, Christian; Gotthardt, Daniel; Weiss, Karl Heinz (Clinics and research in hepatology and gastroenterology, 2020)
Background and aims - Primary sclerosing cholangitis (PSC) is a chronic cholestatic disease that causes liver cirrhosis, leading to liver failure. Additionally, PSC is a risk factor for cholangiocarcinoma. Its mechanism is unknown, and liver transplantation remains the sole curative option. The membrane bound O-acyltransferase domain containing 7 (MBOAT7) rs641738 and rs626283 variant alleles have been associated with both an accelerated progression of the disease and a higher risk for developing a more severe phenotype in many chronic hepatic diseases. Thus, we analysed their effect on long-term outcomes and laboratory parameters in PSC patients. - Methods - We determined MBOAT7 genotypes and estimated the actuarial survival rate free of liver transplantation, using the Kaplan-Meier estimator. The differences between the estimates were analysed using the log-rank test. Patient blood was drawn and analysed for different serum parameters including cholestatic markers. Additionally, MBOAT7 RNA expression in human hepatic cell lines MZCHA1 (a biliary adenocarcinoma cell line), HepG2 (a hepatocellular carcinoma cell line), LX-2 (hepatic stellate cell line) and H-69 (cholangiocyte cell line) was analysed. - Results - Transplant-free survival was significantly prolonged in carriers of two rs641738 variant alleles, which was referred to as the TT genotype (mean 19.6 years; 95% confidence interval [CI]: 16.3-22.9 years) compared to the CC (mean 15.4 years, 95% CI 12.8-18.0 years) and heterozygous genotypes (mean 13.2 years, 95% CI 11.4-15.0 years) (P=0.017). This effect was restricted to male patients. We confirmed the high expression of MBOAT7 in hepatic stellate cells and found that MBOAT7 is less expressed in biliary epithelial cell lines, compared to parenchymal hepatic cells. - Conclusions - Unlike other chronic liver diseases, carrying two MBOAT7 variant alleles does not seem to affect PSC patients negatively, but seems to have a positive effect on transplant-free survival. This study could help improve individual prognosis in PSC patients and give some new perspective on the involvement of the immune system in PSC.